Management of Fatty Liver: What Evidence Says? - Mahtab, Mamun Al (Bangladesh Journal of Medicine, 2023)
Fatty liver is a global pandemic and Bangladesh is no exception. Specially high prevalence of diabetes, improved socio-economic condition is contributing to the growing trend of fatty liver in Bangladesh. Currently there is no definite pharmacologic therapy for fatty liver although some drugs are showing promise and as of now life style modification remains the only option. Bangladesh has a rich heritage of traditional medicine with coexistence of Hekimi or Muslim and Ayurveda or Hindu traditional medicines within the political boundary of today’s Bangladesh. However today’s unfortunate reality remains that in Bangladesh, we have not been able to retain our glory. It is now one of our principal research focuses to revive our traditional herbal medicine. We have already demonstrated the beneficial effects of Glycyrrhiza Glabra (joshtimodhu) in end stage hepatocellular carcinoma. Currently we are focusing on non-alcoholic fatty liver disease. We are exploring the prospects of Kalmegh (Andrographispaniculata), Milk thistle (Silybummarianum), Arjun (Terminaliaarjuna) and Moringa (Moringaoleifera). We are collaborating with a galaxy of public-private universities in our humble effort to revive our glory. Our initial experience with Kalomegh in fatty liver is encouraging. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 188